Investigating constraints in food manufacturing for SMEs performance : a case of Kuala Lumpur - Nur Izaitun Kamaruddin (2018)
Small and medium enterprises (SMEs), across sectors, have proven to be the backbone of the world's economy including Malaysia. However, according to the SME annual report in 2016, 41 percent of businesses have deteriorated in terms of sales and profit, during the third quarter of 2015. Hence, if the deterioration continues, food manufacturing will also face the impacts as 90 percent of the establishments of the food manufacturing are SMEs. Furthermore, food manufacturing is the highest contributor in manufacturing sector of SMEs, in terms of value of gross output, largest number of establishments, and largest number of employments. The deterioration of business proved that there is a presence of constraints that hinder the performance of SMEs. Thus, this study intended to investigate the constraints and their impacts towards SMEs in food manufacturing located in Kuala Lumpur. With the application of Theory of Constraints, five constraints have been identified in the literature that influence the performance of food manufacturing SMEs, namely: (i) institutional constraints, (ii) financial constraints, (iii) external constraints, (iv) internal constraints, and (v) social constraints. A framework consisting of five independent variables and one dependent variable was developed. In order to meet the research objectives, this study employed quantitative method by conducting a self-administered survey questions to 135 SMEs in food manufacturing. The distribution of questionnaires was conducted by hand and through electronic mail. The same method was applied in data collection. The results from correlation and multiple regression have identified that financial, external, and social constraints were significant to the performance of SMEs in food manufacturing. On the other hand, institutional and internal constraints were not significant to the performance. Thus, greater initiatives and collaboration from various parties that are involved directly and indirectly with SMEs in food manufacturing, are needed in order to reduce these constraints. Reduction and elimination of constraints faced by SMEs would enhance the performance of food manufacturing SMEs. This study has managed to produce a model of constraints that have. an impact on the performance of food manufacturing SMEs. In conclusion, this study provided clearer understanding of the food manufacturing practices in Malaysia and offer several implications for research, policymakers, and practitioners.